2010
DOI: 10.1002/ana.21847
|View full text |Cite
|
Sign up to set email alerts
|

High‐frequency electroencephalographic oscillations correlate with outcome of epilepsy surgery

Abstract: Objective-High-frequency oscillations (HFOs) in the intracerebral electroencephalogram (EEG) have been linked to the seizure onset zone (SOZ). We investigated whether HFOs can delineate epileptogenic areas even outside the SOZ by correlating the resection of HFO-generating areas with surgical outcome.Methods-Twenty patients who underwent a surgical resection for medically intractable epilepsy were studied. All had presurgical intracerebral EEG (500Hz filter and 2,000Hz sampling rate), at least 12-month postsur… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

29
559
8
5

Year Published

2011
2011
2019
2019

Publication Types

Select...
7
3

Relationship

2
8

Authors

Journals

citations
Cited by 617 publications
(601 citation statements)
references
References 39 publications
29
559
8
5
Order By: Relevance
“…Subsequent studies have demonstrated that HFOs can be reliably recorded using commercially-available macroelectrodes, both subdural and depth electrodes, with the highest rates during slow-wave NREM sleep. They were found to be an independent epilepsy marker both in neocortical epilepsy and mTLE [17][18][19][20][21][22]. The regions showing high rates of interictal or ictal HFOs spatially colocalize with the SOZ or EZ, and resection of areas with higher interictal or ictal HFO rates have been significantly associated with a better surgical outcome (Table 1).…”
Section: High-frequency Oscillationsmentioning
confidence: 99%
“…Subsequent studies have demonstrated that HFOs can be reliably recorded using commercially-available macroelectrodes, both subdural and depth electrodes, with the highest rates during slow-wave NREM sleep. They were found to be an independent epilepsy marker both in neocortical epilepsy and mTLE [17][18][19][20][21][22]. The regions showing high rates of interictal or ictal HFOs spatially colocalize with the SOZ or EZ, and resection of areas with higher interictal or ictal HFO rates have been significantly associated with a better surgical outcome (Table 1).…”
Section: High-frequency Oscillationsmentioning
confidence: 99%
“…The close relationship between hippocampal fast ripples and individual cell bursting is now widely accepted in the field (Bikson et al, 2003a;Engel et al, 2009;Köhling and Staley, 2011). A major reason to focus at their mechanisms is linked with their potential diagnostic value: if fast ripples are biomarkers of abnormal and enhanced forms of neuronal synchronization, then their detection can be used to closely delineate the epileptogenic territories and to eventually identify candidate areas for resection in combinations with other clinical variables (Jacobs et al, 2010;Zijlmans et al, 2012).…”
Section: Fast Ripples and The Epileptic Hippocampus: The Out-of-phasementioning
confidence: 99%
“…HFOs seem better markers for the SOZ than epileptic spikes and do not depend on the underlying pathology (Jacobs et al, 2008(Jacobs et al, , 2009a. Finally, removal of HFO generating tissue is related to good surgical outcome, more than spikes and the SOZ are (Jacobs et al, 2010), which supports their relation to epileptogenic tissue and potential clinical importance. The current hypothesis is that HFOs result from misconnected or disinhibited neuronal networks leading to highly synchronized neuronal activity over an area of brain tissue, which in turn results in seizure genesis after other areas or networks get involved (Bragin et al, 2004a;Engel et al, 2009;Ogren et al, 2009).…”
Section: Introductionmentioning
confidence: 98%